Kajian Kualitas Air Muara Sungai Musi Sumatera Selatan - Wike Ayu Eka Putri; Melki Melki (Journal of Marine and Aquatic Sciences, 2020)
The Musi River Downstream filled with a variety of activities that potential to cause degradation of environmental quality. This condition can be seen from the color of the waters that tend to be cloudy. This condition can be an indicator that there has been polluted. This study was aimed to explore information about the quality waters of Musi River Estuary from several chemical parameters. Water sampling was conducted in July 2011 at the Musi River Estuary which was divided into 7 research stations. The results showed that nitrate concentrations during tides and lows ranged from 0.01-0.0.9 mg / L, phosphate 0.13-0.14 mg L-1, TSS 30-185 mg L-1, ammonia 0.03-0, 11 mg L-1, TOM 9,48-18,96 mg L-1 and dissolved oxygen 3,32-11,60 mg L-1. Ammonia, dissolved oxygen and TOM parameters are still good and feasible for organism while nitrate, phosphate and TSS have exceeded the permissible threshold for marine life.